Controlled direct electron transfer kinetics of fructose dehydrogenase at cup-stacked carbon nanofibers. Issue 40 (9th October 2017) - Komori, K.; Huang, J.; Mizushima, N.; Ko, S.; Tatsuma, T.; Sakai, Y.
Abstract : The direct electron transfer kinetics of fructose dehydrogenase was controlled by its orientation at the surface of cup-stacked carbon nanofibers with different atomic oxygen/carbon ratios. Abstract : Graphene edge sites not only facilitate heterogeneous electron transfer reactions of redox species because of localization of electrons, but also allow sensitivities and selectivities to be tuned by controlling the atomic oxygen/carbon (O/C) ratio. Here, we immobilized fructose dehydrogenase (FDH) onto the surface of cup-stacked carbon nanofibers (CSCNFs), which provide highly ordered graphene edges with a controlled O/C ratio, and investigated the direct electron communication with FDH. As the O/C ratio decreased at the CSCNF surface, the negative zeta potential was mitigated and the electrochemical communication with FDH was facilitated. This is likely due to improved orientation of FDH molecules on the CSCNF surface. CSCNFs with a controlled O/C ratio could be applied to FDH-basedd -fructose biosensors with tunable dynamic range and fructose biofuel cells with a controlled maximum current.